Despers Earn Most Points in Prelims - Unknown (Daily Express)
WITCO Desperadoes was awarded more points than any other band that took part in the preliminary steelband competitions, in the North, South and East zone. Despers placed first in Panorama North zonal preliminaries with their rendition of Blue Boy's "Rebecca". International Trust Nu-Tones won the East zone and Dunlop Tornadoes won the South zonal preliminaries.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago